Effects of pre-process elicitor immersion on the physicochemical qualities of fresh-cut papaya fruits cv. ‘Holland’ during cold storage - Supapvanich, S.; Sungkra, P.; Phunphed, J. (International Journal of Agricultural Technology, 2020)
Postharvest treatment of elicitors such as salicylic acid (SA) and methyl jasmonate (MeJA) improved postharvest quality of fruit and vegetables. The effect of pre-process immersions on SA or MeJA on the physicochemical quality changes of fresh-cut papaya fruits cv. ‘Holland’ during cold storage is hereby reported. The fruits were immersed in 2 mM SA or 10-4 M MeJA for 1 hour and then stored at room temperature (26 ± 1 °C) for 24 hours before fresh-cut processing. The biochemical parameters such as firmness, total soluble solids (TSS), colour attributes, antioxidant activities and bioactive compounds of fresh-cut papaya fruit during storage at 4 °C for 8 days were monitored. Both SA and MeJA treatments effectively maintained firmness but had no influence on the changes in TSS and colour attributes on storage. Antioxidant capacity of the fresh-cut papaya was enhanced by SA or MeJA immersion. While, free radical scavenging activity was induced by SA immersion. The amounts of total phenols and flavonoids of SA treated fresh-cut papaya fruit were higher than in the control. MeJA immersion induced flavonoids content but not total phenols. The pre-process immersion of SA and MeJA could maintain texture and improve nutritional quality of fresh-cut papaya fruit during storage.